The national parks. Episode three, The empire of grandeur (1915-1919) [videorecording (DVD)] : America's best idea - Burns, Ken, 1953-; Coyote, Peter; Mather, Stephen Tyng, 1867-1930; Mills, Enos A., 1870-1922 (PBS Home Video ; Distributed by Paramount Home Entertainment, 2009)
In the early 20th century, America has a dozen national parks, but they are a haphazard patchwork of special places under the supervision of different federal agencies. The conservation movement, after failing to stop the Hetch Hetchy dam, pushes the government to establish one unified agency to oversee all the parks, leading to the establishment of the National Park Service in 1916. Its first director, Stephen Mather, a wealthy businessman and passionate park advocate who fought vigorously to establish the NPS, launches an energetic campaign to expand the national park system and bring more visitors to the parks. Among his efforts is to protect the Grand Canyon from encroaching commercial interests and establish it as a national park, rather than a national monument.